2017
DOI: 10.1038/npp.2017.69
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Regional Brain Glucose Metabolism Following Opioid Withdrawal and Replacement

Abstract: Methadone and buprenorphine are currently the most common pharmacological treatments for opioid dependence. Interestingly, the clinical response to these drugs appears to be sex specific. That is, females exhibit superior therapeutic efficacy, defined as extended periods of abstinence and longer time to relapse, compared with males. However, the underlying metabolic effects of opioid withdrawal and replacement have not been examined. Therefore, using FDG and microPET, we measured differences in regional brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 87 publications
2
11
0
Order By: Relevance
“…In a recent report of health-related quality of life (EQ-5D-5L), it was concluded that men score increased mean values using the visual analog scale (VAS) than women, and that, overall, the VAS mean decreases with age (62). Santoro et al (63) found significant sex differences in regional brain glucose metabolism associated with opioid withdrawal. However, this study was performed in a different setting of patients and with a different treatment goal.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report of health-related quality of life (EQ-5D-5L), it was concluded that men score increased mean values using the visual analog scale (VAS) than women, and that, overall, the VAS mean decreases with age (62). Santoro et al (63) found significant sex differences in regional brain glucose metabolism associated with opioid withdrawal. However, this study was performed in a different setting of patients and with a different treatment goal.…”
Section: Discussionmentioning
confidence: 99%
“…For example, estrogens can diminish opioids' antinociceptive effects [132], there is evidence of interactions and crosstalk between opioid and estrogen receptors [133], and estrogens may impact the antinociceptive and rewarding effects of methadone through effects on methadone metabolism [134]. In addition, recent preclinical work suggests sex-specific effects of acute opioid withdrawal and subsequent opioid replacement (with methadone or buprenorphine) on regional brain metabolism within regions including the anterior cingulate, amygdala and striatum [135,136]. Thus, neuroimaging studies including equal numbers of male and female participants that are specifically powered to detect sex-specific effects are urgently needed in OUD.…”
Section: Discussionmentioning
confidence: 99%
“…In the pilot study, we found that (1) Neuropharmacological studies show that multiple regions of the brain with high opioid receptors, are related to MW or drug abuse in human and animals 13, 15, 32-41 . Anatomical, and neurochemical studies have implicated an important role of the PAG in opioid withdrawal [15][16][17][18][42][43][44] . Distinct PAG columns project to midline and intralaminar thalamic regions 45 .…”
Section: Discussionmentioning
confidence: 99%
“…locus ceruleus (LC), periaqueductal gray (PAG)) of the brain with high opioid receptors, are related to MW or drug abuse [12][13][14] . Functional and anatomical studies have implicated an important role for the PAG in opioid withdrawal [15][16][17][18] . Sirtuins are protein deacetylases dependent on nicotine adenine dinucleotide (NAD) in organisms ranging from bacteria to humans 19 .…”
Section: Introductionmentioning
confidence: 99%